Improving Australia's schools : executive summary of Making schools more effective : report of the Australian Effective Schools Project - Piper, Kevin; Banks, Diana; Evans, Beryl; McGaw, Barry (Hawthorn, Vic : Australian Council for Educational Research, 1993)
This is an executive summary of Making Schools More Effective: Report of the Australian Effective Schools Project.
Keywords: Education; School management and organization -- Australia; School improvement programs -- Australia; Education -- Aims and objectives -- United States